Innovation Level of Adopting Storytelling for Msme’s Business Sustainability in Marketing Activity - PAMUNGKAS, Indra Novianto Adibayu; SUNARTO, Sunarto; SIGIT, Ridzki Rinanto (PT Keberlanjutan Strategis Indonesia, 2023)
Digitalization makes adaptation a new demand that MSMEs, particularly in the microbusiness sector, must comply with. Unfortunately, this sector has a lower rate of adopting digital content for promotion purposes. Since the advent of social media, storytelling has become one of the most popular types of digital marketing material, and It also has the added benefit of preventing advertising from being rejected. This research is quantitative, using a survey of microbusiness owners in West Java, Indonesia. The results of the hypothesis test show that compatibility and social influence are the two most important predictors of adoption rates, with compatibility showing the highest adoption rate for the acceptance of all indicators of storytelling as digital material except mythology. West Java is one of the areas with aspects of mythology and cultural stories mixed with stories and tales; yet, culture is viewed as an ambiguous notion when connected to consumer behavior intellectually, practically, and legally.